Nostalgic photographs in the contemporary image ecology: the example of Tyrrells crisp packaging. Issue 1 (1st January 2018) - Wagner, Karin
ABSTRACT: This article concerns how nostalgic photographs are circulated in new contexts such as packaging and social media. The purpose is to explore the ontological transformations of photographs in the contemporary image ecology, blurring the categories "analogue" and "digital". What new meanings and materiality can old photographs acquire when for instance put on packages that are used, thrown away, recycled and sometimes upcycled? The crisp producer Tyrrells is used as a case study, since quirky old photographs is a vital part of their packaging design, as well as on their website and social media channels. The company makes use of Monty Python-style collages to conjure up the English eccentric and their marketing communication is characterised by ironic nostalgia. Although the package is a throw away object, it can be upcycled by craft makers and sold at online marketplaces, which means that the photographs continue their circulation, from analogue film and cameras, to press agencies, to the printed page, to stock image databases on the Internet, to crisp packages and birthday cards, to Facebook and Instagram, to crafted bags in digital marketplaces and so forth. The package has a twofold appearance, as a physical object and as a virtual object on the web, both of which constitute the other. The ontology of the photograph has changed, since the different forms of appearance can no longer be disentangled from each other and join hands in the trajectory of the photograph in the contemporary image ecology.